(untitled) - Donald, Ralph (Ames, Iowa, 2000)
Fundamentals of Television Production is a comprehensive, in-depth text for both basic and advanced television production courses. Authors Ralph Donald and Thomas Spann have provided a number of unique features: ey terms and definitions at the end of each chapter; Over 400 photos and figures; Coverage of equipment, old and new, from a history of videotape to new developments in high-definition TV; Through explanations of highly technical and theoretical topics
Keywords: Television,Truyền hình; Production and direction,Ssản xuất chương trình